Employment Alignment and Salary Satisfaction among Doctoral-Level High-Skilled Talent in Taiwan - Chuang, Yih-chyi; Hsueh, Yung Lin Chen (Journal of Education and Learning Environments, 2026)
Taiwan has invested substantially in doctoral education to maintain competitiveness in technology-intensive industries, yet empirical evidence reveals a significant puzzle: while 73% of doctorate holders report high education-employment alignment, only 38% express satisfaction with their salaries, and approximately one-third intend to work overseas within five years. This study analyzes labor market outcomes for 4790 doctoral degree holders using the 2016 Doctoral Mobility Intentions Survey to understand employment alignment, salary determinants, and overseas migration intentions. The analysis reveals an "alignment-satisfaction paradox" where high education-job matching does not translate into salary satisfaction due to expectation formation, international comparison effects, and regional employment constraints. Key findings indicate that younger individuals, those with prior work experience, and those with overseas experience demonstrate higher alignment. However, engineering graduates exhibit substantially lower alignment due to theory-practice gaps in doctoral curricula and mismatches with Taiwan’s semiconductor-centered industrial structure. Practical work experience, overseas employment exposure, and full-time employment during doctoral studies positively impact both absolute salaries and satisfaction levels. The study reveals that addressing brain drain and improving human capital utilization requires multifaceted policy responses beyond curriculum reform alone, including compensation competitiveness in public sectors, regional industrial development, and institutional reforms linking doctoral training to strategic industry needs. Discipline-specific policy interventions are recommended: engineering curriculum reform with mandatory internships and dual-track doctorates; humanities/social sciences salary enhancement and private-sector demand expansion; science/medicine research ecosystem strengthening; and central Taiwan industrial upgrading.